Analisis Kesalahan Penggunaan Bahasa Indonesia dalam Artikel Ilmiah SMA Al Khoiriyah Sumbergempol - Hidayah, Sa'adatun Nuril; Setyawan, Bagus Wahyu; Rakhmawati, Ani; Tawandorloh, Ku-Ares (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2024)
The purpose of learning Indonesian is to hone students' language skills. One of the things that is developed is the skill of writing scientific articles. In practice, there are still many errors in students' scientific article work. For this reason, the purpose of this study is to describe and analyze the misuse of the Indonesian language in scientific articles of students of Al Khoiriyah Sumbergempol High School. The data source of this research is 34 articles by students. The data collection technique used in this study is a documentary study technique and is assisted by an instrument in the form of a data recording card. The analysis of research data includes the stages of data reduction, data presentation, and conclusion drawn. The results of data analysis found two categories of errors, namely errors in the use of spelling and errors in the preparation of the structure of scientific articles. Writing errors include mistakes in the use of letters, use of words, use of punctuation, and writing terms/absorption of foreign languages. Structural errors include errors in the preparation of titles, abstracts, editorial sections, research results, and conclusion/closing sections. This is important to be a concern and a reflection material for future learning as well as prepare the skills of students who will continue their studies in higher education.